Negative electrode active material for secondary battery, method for producing the same, and secondary battery including the same
Silicon-based particles with M-O-Si bonds, produced from waste glass, address the volume change issue in lithium-ion batteries, enhancing electrochemical performance and environmental sustainability.
Patent Information
- Application Number
- JP2024543405
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-25
- Filing Date
- 2022-11-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-11-25
AI Technical Summary
Silicon-based negative electrode materials for lithium-ion secondary batteries suffer from significant volume changes during charging and discharging, leading to cracking and separation from the electrode, which compromises their electrochemical properties.
The use of silicon-based particles with M-O-Si bonds, where M is a metal such as B, P, Ge, Ti, or Zr, produced through low-temperature reduction of waste glass containing silica and metal oxides, helps control volume changes and improve electrochemical properties.
The solution suppresses volume changes during charging and discharging, enhances electrochemical performance, and recycles waste glass, reducing environmental pollution while lowering raw material costs and improving purity.
Smart Images

Figure 2025502467000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode active material for a secondary battery, a method for producing the same, and a secondary battery including the same. [Background technology]
[0002] In the field of lithium-ion secondary batteries, silicon anode material has been attracting attention as a next-generation battery anode material because it has a theoretical capacity per weight that is more than 10 times that of commercially available graphite material (370mAh / g).
[0003] However, there is a problem that the volume of the battery increases by more than 300% due to the reaction between lithium ions and silicon during charging. When the battery is repeatedly charged and discharged, the large volume change can cause the silicon to crack and become separated from the electrode. Summary of the Invention [Problem to be solved by the invention]
[0004] According to an embodiment, a negative electrode active material for a secondary battery is provided that is suppressed in volume change during repeated charging and discharging and has excellent electrochemical properties.
[0005] In another embodiment, a method for manufacturing the negative electrode active material for a secondary battery is provided.
[0006] In yet another embodiment, a secondary battery including the negative electrode active material for a secondary battery is provided. [Means for solving the problem]
[0007] An embodiment provides a negative electrode active material for a secondary battery, comprising silicon (Si)-based particles, the silicon (Si)-based particles including an MO-Si bond (wherein M is a metal).
[0008] The metal (M) may include B, P, Ge, Ti, Zr, or a combination thereof.
[0009] The silicon (Si)-based particles may further include Si-Si bonds.
[0010] The silicon (Si)-based particles can be produced by reducing waste glass containing silica and metal oxides at a temperature of 200°C to 350°C.
[0011] The silicon (Si)-based particles have a Fourier transform infrared (FT-IR) spectrum of 800 cm -1 ~900cm -1 Wave number: 650cm -1 ~750cm -1 The transmittance peak corresponding to the MO-Si bond can be observed at wavenumbers of 100, 150, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 19
[0012] The silicon (Si)-based particles may have an average particle size of 0.05 μm to 5 μm.
[0013] Another embodiment provides a method for preparing a negative electrode active material for a secondary battery, the method comprising the steps of: reducing waste glass containing silica and metal oxide at a temperature of 200°C to 350°C to prepare silicon (Si)-based particles, the prepared silicon (Si)-based particles including MO-Si bonds (wherein M is a metal).
[0014] The waste glass may be thermally strengthened glass generated during disposal of displays.
[0015] The metal of the metal oxide and the metal (M) may include B, P, Ge, Ti, Zr, or combinations thereof.
[0016] The reduction may be carried out by introducing a reducing agent including Al, AlCl3, Zn, Mg, Ca, or a combination thereof.
[0017] In yet another embodiment, a secondary battery includes a negative electrode including the negative electrode active material; a positive electrode; and an electrolyte.
[0018] The capacity of the negative electrode can be from 800mAh / g to 1700mAh / g at 1C.
[0019] The negative electrode may have a volume change of 5% to 40% after 50 cycles of charging and discharging at 0.5C. Effect of the Invention
[0020] The negative electrode active material for a secondary battery according to an embodiment can improve the electrochemical properties of the secondary battery by suppressing volume change that occurs during repeated charging and discharging, and can also be environmentally friendly since it can be recycled from waste glass of various displays. [Brief description of the drawings]
[0021] [Figure 1a] 2 is a scanning electron microscope (SEM) image of negative electrode active materials for secondary batteries according to Example 1 and Comparative Example 1, respectively. [Figure 1b] 2 is a scanning electron microscope (SEM) image of negative electrode active materials for secondary batteries according to Example 1 and Comparative Example 1, respectively. [Figure 2a] 2 is an X-ray diffraction analysis (XRD) graph of negative electrode active materials for secondary batteries according to Example 1 and Comparative Example 1, respectively. [Figure 2b] 2 is an X-ray diffraction analysis (XRD) graph of negative electrode active materials for secondary batteries according to Example 1 and Comparative Example 1, respectively. [Figure 3a] 1 is a graph showing Fourier transform infrared (FT-IR) spectra of negative electrode active materials for secondary batteries according to Example 1 and Comparative Example 1, respectively. [Figure 3b] 1 is a graph showing Fourier transform infrared (FT-IR) spectra of negative electrode active materials for secondary batteries according to Example 1 and Comparative Example 1, respectively. [Figure 4a] 2 is a graph showing changes in voltage and discharge capacity due to initial charge / discharge cycles in the secondary batteries according to Example 1 and Comparative Example 1, respectively. [Figure 4b]2 is a graph showing changes in voltage and discharge capacity due to initial charge / discharge cycles in the secondary batteries according to Example 1 and Comparative Example 1, respectively. [Figure 5a] 2 is a graph showing the capacity change due to repeated charge / discharge cycles in the secondary batteries according to Example 1 and Comparative Example 1, respectively. [Figure 5b] 2 is a graph showing the capacity change due to repeated charge / discharge cycles in the secondary batteries according to Example 1 and Comparative Example 1, respectively. [Figure 6a] 2 is an image showing a change in volume of the negative electrode when the secondary batteries according to Example 1 and Comparative Example 1 are repeatedly charged and discharged. [Figure 6b] 2 is an image showing a change in volume of the negative electrode when the secondary batteries according to Example 1 and Comparative Example 1 are repeatedly charged and discharged. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Although the present invention will be described in detail below so that those skilled in the art can easily implement the present invention, the present invention may be embodied in many different forms and is not limited to the embodiments described herein.
[0023] According to an embodiment, a negative electrode active material for a secondary battery includes silicon (Si)-based particles, and the silicon (Si)-based particles include MO-Si bonds (wherein M is a metal).
[0024] In one embodiment, the silicon (Si)-based particles used as the negative electrode active material contain MO-Si bonds, and therefore the volume change of silicon (Si) that occurs when reacting with lithium ions can be controlled. In other words, by using silicon (Si) containing MO-Si bonds as the negative electrode active material, the volume change of silicon that occurs during repeated charging and discharging can be suppressed, and thus the electrochemical characteristics of the secondary battery can be improved.
[0025] Specifically, the MO-Si bond may be a particle having the MO-Si bond. In other words, the silicon (Si)-based particle may be in the form of agglomeration of a plurality of particles, and one of the plurality of particles may include a particle having the MO-Si bond.
[0026] In the MO-Si bond, the metal (M) can include B, P, Ge, Ti, Zr, or a combination thereof.
[0027] According to an embodiment, the silicon (Si)-based particles have pure Si-Si bonds as well as the MO-Si bonds. Specifically, according to X-ray diffraction analysis (XRD) and Fourier transform infrared (FT-IR) spectrum of the silicon (Si)-based particles, the particles have pure Si-Si bonds and additionally have MO-Si bonds. Here, the Si-Si bonds may be particles having Si-Si bonds.
[0028] More specifically, the silicon (Si)-based particles have a Fourier transform infrared (FT-IR) spectrum of 800 cm -1 ~900cm -1 Wave number: 650cm -1 ~750cm -1 The transmittance peak corresponding to the MO-Si bond may be, for example, at a wave number of 850 cm -1 ~900cm -1 Wave number: 650cm -1 ~700cm -1 or a combination of these wave numbers.
[0029] The silicon (Si)-based particles may have an average particle size of 0.05 μm to 5 μm, for example, 0.05 μm to 1 μm, or 0.1 μm to 0.8 μm. When the average particle size of the silicon (Si)-based particles is within the above range, an electrode with high capacity can be obtained.
[0030] The silicon (Si)-based particles can be prepared by a low-temperature reduction method using waste glass containing silica and metal oxides.
[0031] The waste glass may be heat-strengthened glass used in display liquid crystal of smartphones, etc. Most of the waste glass generated when various displays are discarded is landfilled without being recycled, which causes environmental pollution. In one embodiment, the waste glass is used as a raw material for a negative electrode active material, so that the waste glass of various displays can be recycled, thereby reducing environmental pollution, which is environmentally friendly.
[0032] In addition, the conventional process for producing silicon from silica requires a temperature of 1700°C or higher when using a carbothermal process, and when using a metal reducing agent such as magnesium or aluminum, it is difficult to control the structure due to an exothermic reaction of 2500°C or higher. On the other hand, one embodiment uses waste glass, so there is no need for equipment for high-temperature processes, which not only significantly reduces raw material costs, but also makes it easy to control the structure through a low-temperature reduction method, and produces silicon with high purity.
[0033] Specifically, silicon (Si)-based particles according to an embodiment may be prepared by reducing waste glass containing silica and metal oxides at a temperature of 200°C to 350°C, for example, 200°C to 300°C, 200°C to 280°C.
[0034] When produced at a low reduction temperature within the above range, it is easy to control the structure, and silicon-based particles with high purity can be obtained. Since the produced silicon-based particles contain MO-Si bonds, the volume change of silicon (Si) that occurs during charging and discharging can be prevented.
[0035] The metal of the metal oxide is the same as the metal (M) in the MO-Si bond. For example, the metal oxide can include boron oxide, phosphorus oxide, germanium oxide, titanium oxide, zirconium oxide, or a combination thereof.
[0036] The silicon (Si)-based particles may be prepared by adding a reducing agent. The reducing agent may include Al, AlCl3, Zn, Mg, Ca, or a combination thereof. For example, Al and AlCl3 may be used together as the reducing agent, and in this case, they may be mixed at a weight ratio of 1:5 to 1:20, for example, 1:10 to 1:20.
[0037] Hereinafter, a secondary battery including the above-mentioned negative electrode active material will be described.
[0038] The secondary battery includes a negative electrode, a positive electrode, and an electrolyte.
[0039] A negative electrode using the silicon (Si)-based particles according to an embodiment as a negative electrode active material may have a high capacity, specifically, 800mAh / g to 1700mAh / g at 1C, for example, 800mAh / g to 1500mAh / g at 1C, or 900mAh / g to 1200mAh / g at 1C.
[0040] The negative electrode using the silicon (Si)-based particles according to an embodiment as a negative electrode active material may suppress volume change that occurs during repeated charging and discharging. Specifically, the volume change after 50 cycles of charging and discharging at 0.5C may be 5% to 40%, for example, 5% to 20%, or 10% to 18%.
[0041] The negative electrode includes a current collector and a negative electrode active material layer disposed on the current collector.
[0042] The current collector may be, but is not limited to, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.
[0043] The negative electrode active material layer may include the above-mentioned negative electrode active material, and may further include a binder and a conductive material.
[0044] The binder serves to effectively adhere each of the negative electrode active material particles to each other and also to effectively adhere the negative electrode active material to the negative electrode current collector. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.
[0045] The conductive material is used to impart conductivity to the electrodes, and any material can be used as long as it does not cause a chemical change in the constructed battery and is electronically conductive. Examples of the conductive material that can be used include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fibers; metal-based materials such as metal powders or metal fibers of copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and conductive materials containing mixtures of these.
[0046] The positive electrode includes a current collector and a positive electrode active material layer disposed on the current collector.
[0047] The current collector may be made of aluminum, but is not limited thereto.
[0048] The positive electrode active material layer includes a positive electrode active material. As the positive electrode active material, a compound capable of reversible intercalation and deintercalation of lithium (lithiated intercalation compound), specifically, a lithium metal oxide, can be used. As the lithium oxide, specifically, an oxide containing lithium and at least one metal selected from cobalt, manganese, nickel, and aluminum can be used.
[0049] The positive electrode active material layer may further include a binder and a conductive material.
[0050] The binder serves to effectively adhere each positive electrode active material particle to each other and also to effectively adhere the positive electrode active material to the positive electrode current collector. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, and nylon.
[0051] The conductive material is used to impart conductivity to the electrodes, and any material can be used as long as it does not cause a chemical change in the constructed battery and is electronically conductive. Examples of the conductive material that can be used include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fibers; metal-based materials such as metal powders or metal fibers of copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and conductive materials containing mixtures of these.
[0052] The negative electrode and the positive electrode are prepared by mixing an active material, a conductive material, and a binder in a solvent to prepare an active material composition, and then coating the composition on a current collector. The method of preparing such an electrode is widely known in the art, and therefore will not be described in detail in this specification. The solvent may be, but is not limited to, N-methylpyrrolidone.
[0053] The electrolyte includes a lithium salt and an organic solvent.
[0054] The lithium salt is a material that is dissolved in an organic solvent and acts as a source of lithium ions in a secondary battery, enabling basic operation of the secondary battery, and promoting the movement of lithium ions between the positive electrode and the negative electrode.
[0055] Representative examples of the lithium salt include LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO3C2F5)2, LiN(CF3SO2)2, LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 Examples of the lithium oxynitride include lithium oxynitride (LiO2), lithium oxynitride (LiBOB), lithium oxynitride (LiSO2), lithium oxynitride (LiCl), lithium oxynitride (LiI), lithium oxynitride (LiBOB ...
[0056] The concentration of the lithium salt may be within a range of about 0.1 M to about 2.0 M. When the concentration of the lithium salt is within this range, the gel electrolyte composition has appropriate conductivity and viscosity, so that the gel electrolyte composition can exhibit excellent electrolyte performance and lithium ions can move effectively.
[0057] The organic solvent serves as a medium through which ions involved in the electrochemical reaction of the secondary battery can move. The organic solvent is a non-aqueous organic solvent and may be selected from carbonate-based solvents, ester-based solvents, ether-based solvents, ketone-based solvents, alcohol-based solvents, and aprotic solvents.
[0058] Examples of the carbonate-based solvent that can be used include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), ethylmethyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC).
[0059] In particular, when a chain carbonate compound and a cyclic carbonate compound are mixed and used, it is preferable because a solvent having a high dielectric constant and low viscosity can be produced. In this case, the cyclic carbonate compound and the chain carbonate compound can be mixed and used in a volume ratio of about 1:1 to 1:9.
[0060] Examples of the ester-based solvent include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, and caprolactone. Examples of the ether-based solvent include dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, and tetrahydrofuran. Examples of the ketone-based solvent include cyclohexanone. Examples of the alcohol-based solvent include ethyl alcohol and isopropyl alcohol.
[0061] The organic solvents may be used alone or in combination of one or more thereof. When using in combination of one or more thereof, the mixing ratio may be appropriately adjusted depending on the desired performance of the battery.
[0062] Depending on the type of secondary battery, a separator may be present between the positive electrode and the negative electrode. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer film of two or more layers of these can be used, and it is natural that a mixed multilayer film such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, or a polypropylene / polyethylene / polypropylene three-layer separator can be used. EXAMPLES
[0063] Hereinafter, specific examples of the present invention will be presented. However, the examples described below are merely for the purpose of specifically illustrating or explaining the present invention, and the present invention should not be limited thereby. In addition, since the contents not described here can be sufficiently inferred by those skilled in the art, the description thereof will be omitted.
[0064] (Production of silicon-based particles)
[0065] Example 1
[0066] Silicon (Si)-based particles were produced by low-temperature reduction using borosilicate glass (neutral borosilicate glass 5.1, USP and EP Type 1 glass) (containing SiO2 85%, B2O3 13%, and Na 2%), waste glass generated during the disposal of smartphones, and reducing agents Al and AlCl3. Specifically, borosilicate glass was mixed with Al and AlCl3 in a weight ratio of 1:0.8:8, and then placed in a stainless steel reactor (Unilok Corporation), and reacted in an argon atmosphere at 250℃ for 15 hours to produce silicon-based particles. Impurities were then removed through chemical etching using an HCl solution.
[0067] Comparative Example 1
[0068] Bare silica (SiO2 99.5%, 400 mesh, 2 micron APS powder, SA surface area 2m 2 Silicon-based particles were produced by mixing 1:0.8:8 Al and AlCl3 in a weight ratio of 1:0.8:8 in a stainless steel reactor (Unilok Corporation) and reacting in an argon atmosphere at 250°C for 15 hours. Then, impurities were removed by chemical etching using an HCl solution.
[0069] (Manufacture of negative electrodes for secondary batteries) The silicon-based particles prepared in Example 1 and Comparative Example 1 as negative active materials, carbon black as a conductive material, and polyacrylic acid (PAA) as a binder were added to water as a solvent in a weight ratio of 60:20:20 to prepare negative electrode mixture slurries (solid content: 50 wt%). The negative electrode mixture slurries were applied to a copper (Cu) thin film as a negative electrode current collector having a thickness of 20 μm, and then dried to prepare negative electrodes.
[0070] Evaluation 1: Scanning electron microscope (SEM) measurement of negative electrode active material The surfaces of the silicon-based particles prepared as the negative electrode active materials in Example 1 and Comparative Example 1 were measured using a scanning electron microscope (SEM), and the results are shown in FIGS. 1a and 1b.
[0071] 1a and 1b are scanning electron microscope (SEM) images of negative electrode active materials for secondary batteries according to Example 1 and Comparative Example 1, respectively.
[0072] 1a and 1b, it can be seen that silicon-based particles having a size of 1 micrometer or less were produced in Example 1. Also, it can be seen that silicon-based particles having a size of 1 micrometer or less were produced in Comparative Example 1, and that the surfaces were smooth.
[0073] Evaluation 2: X-ray diffraction analysis (XRD) measurement of negative electrode active material X-ray diffraction analysis (XRD) was performed on the silicon-based particles prepared in Example 1 and Comparative Example 1 as the negative electrode active material, and the results are shown in FIGS. 2a and 2b.
[0074] 2a and 2b are X-ray diffraction analysis (XRD) graphs of the negative electrode active materials for secondary batteries according to Example 1 and Comparative Example 1, respectively.
[0075] 2a and 2b, it can be seen that pure silicon (Si) particles are synthesized within the silicon-based particles produced in Example 1, while unreacted silica (SiO2) particles remain even after etching with HCl in the silicon-based particles produced in Comparative Example 1. This shows that the silicon-based particles according to one embodiment contain MO-Si bonds but have high silicon (Si) purity.
[0076] Evaluation 3: Fourier transform infrared (FT-IR) measurement of negative electrode active material The silicon-based particles prepared in Example 1 and Comparative Example 1 as negative active materials were subjected to Fourier transform infrared (FT-IR) measurement, and the results are shown in FIGS. 3a and 3b.
[0077] 3a and 3b are graphs showing Fourier transform infrared (FT-IR) spectra of the negative electrode active materials for secondary batteries according to Example 1 and Comparative Example 1, respectively.
[0078] 3a and 3b, it can be seen that the silicon-based particles prepared in Example 1 contain pure Si-Si bonds and additionally have BO-Si bonds and Si-O-Si bonds. On the other hand, it can be seen that the silicon-based particles prepared in Comparative Example 1 only have Si-O-Si bonds and Si-Si bonds due to remaining silica. This shows that the silicon-based particles according to one embodiment are particles containing MO-Si bonds.
[0079] Evaluation 4: Measurement of electrochemical characteristics of secondary batteries Half cells were prepared using the negative electrodes and Li counter electrodes prepared according to Example 1 and Comparative Example 1. The half cells were subjected to an initial charge-discharge cycle at 0.05 C, and the resulting discharge capacities are shown in Figures 4a and 4b.
[0080] 4a and 4b are graphs showing the changes in voltage and discharge capacity due to the initial charge-discharge cycles in the secondary batteries according to Example 1 and Comparative Example 1, respectively.
[0081] 4a and 4b, it was confirmed that the discharge capacity of Example 1 was about 1500 mAh / g, and the discharge capacity of Comparative Example 1 was about 1800 mAh / g.
[0082] After the initial charge-discharge cycle, a long-term life test was performed using a 1C fast charge-discharge experiment, and the results are shown in Figures 5a and 5b.
[0083] 5a and 5b are graphs showing the capacity change due to repeated charge / discharge cycles in the secondary batteries according to Example 1 and Comparative Example 1, respectively.
[0084] 5a and 5b, it can be seen that in Example 1, a capacity of about 1000 mAh / g is maintained up to 200 cycles, while in Comparative Example 1, almost no capacity is realized at 100 cycles. That is, it can be seen that Comparative Example 1 cannot withstand the volume change that occurs when charging and discharging are repeated, resulting in a decrease in capacity.
[0085] Therefore, when silicon-based particles including MO-Si bonds are used as a negative electrode active material according to an embodiment, it can be seen that the volume change of the negative electrode is suppressed and the electrochemical properties are improved.
[0086] Evaluation 5: Measurement of volume change of negative electrode Half cells were prepared using the negative electrodes and Li counter electrodes prepared in Example 1 and Comparative Example 1. The half cells were subjected to an initial charge-discharge cycle at 0.05 C, and 50 charge-discharge cycles at 0.5 C were repeated, after which the volume change of the negative electrode was measured, and the results are shown in Figures 6a and 6b.
[0087] 6a and 6b are images showing the volume change of the negative electrode when the secondary batteries according to Example 1 and Comparative Example 1 are repeatedly charged and discharged.
[0088] 6a and 6b, it can be seen that the volume of Example 1 expanded by about 16%, while the volume of Comparative Example 1 expanded by about 225%. That is, it can be seen that the volume change of Comparative Example 1 is not controlled by repeated charging and discharging.
[0089] Therefore, according to an embodiment, when silicon-based particles including MO-Si bonds are used as a negative electrode active material, the volume change of the negative electrode is suppressed.
[0090] Although the above describes a preferred embodiment of the present invention, the present invention is not limited thereto, and can be embodied in various modified forms within the scope of the claims, the detailed description of the invention, and the accompanying drawings, which of course also fall within the scope of the present invention.
Claims
1. Contains silicon (Si) based particles, The silicon (Si)-based particles include an MO-Si bond (wherein M is a metal).
2. 2. The negative electrode active material for a secondary battery according to claim 1, wherein the metal (M) comprises B, P, Ge, Ti, Zr, or a combination thereof.
3. 2. The negative electrode active material for a secondary battery according to claim 1, wherein the silicon (Si)-based particles further contain Si-Si bonds.
4. 2. The negative electrode active material for a secondary battery according to claim 1, wherein the silicon (Si)-based particles are produced by reducing waste glass containing silica and metal oxide at a temperature of 200 to 350°C.
5. The silicon (Si)-based particles have a Fourier transform infrared (FT-IR) spectrum of 800 cm -1 ~900cm -1 Wave number: 650 cm -1 ~750cm -1 2. The negative electrode active material for secondary batteries according to claim 1, which shows a transmittance peak corresponding to the M-O-Si bond at a wave number of 1000 Hz or a wave number of a combination thereof.
6. 2 . The negative electrode active material for a secondary battery according to claim 1 , wherein the silicon (Si)-based particles have an average particle size of 0.05 μm to 5 μm.
7. The method includes reducing waste glass containing silica and metal oxides at a temperature of 200° C. to 350° C. to produce silicon (Si)-based particles, The silicon (Si)-based particles thus produced contain an MO-Si bond (wherein M is a metal).
8. The method for producing a negative electrode active material for a secondary battery according to claim 7 , wherein the waste glass is thermally strengthened glass generated when a display is discarded.
9. The method for producing a negative electrode active material for a secondary battery according to claim 7 , wherein the metal of the metal oxide and the metal (M) include B, P, Ge, Ti, Zr, or a combination thereof.
10. The reduction is performed with Al, AlCl 3 8. The method for producing a negative electrode active material for a secondary battery according to claim 7, wherein the method is carried out by adding a reducing agent containing one of Zn, Mg, Ca, or a combination thereof.
11. A negative electrode comprising the negative electrode active material according to any one of claims 1, 2, and 4 to 6; A positive electrode; and an electrolyte.
12. The secondary battery according to claim 11 , wherein the capacity of the negative electrode is 800 mAh / g to 1700 mAh / g at 1C.
13. The secondary battery according to claim 11 , wherein the negative electrode has a volume change of 5% to 40% after 50 cycles of charging and discharging at 0.5 C.
Citation Information
Patent Citations
Negative electrode active material particle and manufacturing method therefor, negative electrode, battery, and conductive particle
JP2016152213A
Negative electrode active material, negative electrode sheet using the same, electrochemical device, and electronic device
JP2022504057A
Negative electrode active material for nonaqueous electrolyte rechargeable battery and rechargeable battery including the same
KR1020150113771A
Negative electrode material, negative electrode for lithium ion secondary battery, lithium ion secondary battery, and process for producing same
WO2015177830A1